Pulmonary Pleomorphic Carcinoma: A Rare Entity Revisited! - K, Deshmukh Mahesh; S, Galani Komal; Manisha, Mishra; Pooja, Ingale (Journal of Pulmonology and Respiratory Research, 2025)
Introduction: Pleomorphic Carcinoma (PC) is a subset of poorly differentiated non–small cell lung cancer that is diagnostically challenging because it is a rare malignancy of the lung. It shows varying dual-cell components; spindle or giant cells and epithelial cells. Method: We report a case of 68-year-old non-smoking female who presented with cough, fever, pain in the left side of chest & weight loss of recent onset and an abnormal shadow on her chest X-ray. Computed tomography of chest revealed a well defined heterogeneously enhancing cavitatory soft tissue lesion in the posterior basal segment of the left lower lobe with mediastinal lymphadenopathy. Results: Fine needle aspiration cytology& percutaneous lung biopsy confirmed poorly differentiated malignant tumor. Patient underwent a left lower lobectomy. A diagnosis of PC was confirmed after Immunohistochemistry (IHC). Mutation analysis revealed an EGFR exon 21 mutation within the tumor cells. The patient is on Gefitinib based chemotherapy and has remained disease-free for three years post-surgery. Conclusion: PC of the lung is a rare pathological entity. Definite diagnosis may only be made on a resected tumor along with the use of IHC. Surgical resection is the main modality of the treatment. Such rare cases should be documented to establish an optimal management plan and to provide a further insight to targeted therapy.